1988
DOI: 10.1128/mcb.8.8.3345
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor induces multisite phosphorylation of pp60c-src and increases its protein-tyrosine kinase activity.

Abstract: We have shown previously that pp69>-sc is a substrate for protein kinase C in vitro and in vivo and that the target of protein kinase C phosphorylation in mammalian pp6OcSrc is serine 12. We now demonstrate that in addition to tumor promoters, all activators of phosphatidylinositol turnover that we have tested in fibroblasts (platelet-derived growth factor, fibroblast growth factor, serum, vasopressin, sodium orthovanadate, and prostaglandin F2.) lead to the phosphorylation of pp60c-sr at serine 12. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
112
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(117 citation statements)
references
References 75 publications
(68 reference statements)
4
112
1
Order By: Relevance
“…Pancreata or islets were lysed in modified RIPA lysis buffer, 37 and the protein concentrations in the supernatant were determined using the BCA protein assay reagent (Pierce; Rockford, IL). Equal protein concentrations (50 µg) were denatured in a gel loading buffer at 85 o C for 5 minutes and then loaded onto 10 % SDS-polyacrylamide slab gels and transferred to polyvinylidene difluoride membranes and incubated at 4 o C overnight with primary mouse monoclonal osteopontin antibody, 1:150 diluted in PBST (Santa Cruz Biotechnology, Santa Cruz, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Pancreata or islets were lysed in modified RIPA lysis buffer, 37 and the protein concentrations in the supernatant were determined using the BCA protein assay reagent (Pierce; Rockford, IL). Equal protein concentrations (50 µg) were denatured in a gel loading buffer at 85 o C for 5 minutes and then loaded onto 10 % SDS-polyacrylamide slab gels and transferred to polyvinylidene difluoride membranes and incubated at 4 o C overnight with primary mouse monoclonal osteopontin antibody, 1:150 diluted in PBST (Santa Cruz Biotechnology, Santa Cruz, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Since phosphorylation of Thr-654 by PKC suppresses epidermal growth factor receptor activity (8,16), it is plausible that Ser-12 phosphorylation regulates pp60c-'r( activity. Biochemical studies have detected no change in pp60c"`in vitro kinase activity after either in vitro or in vivo phosphorylation at Ser-12 (10)(11)(12)29); however, these assays would not be sensitive to in vivo effects that involve interactions between pp6Oc"rc and other proteins. Genetic studies to detect such effects have not yet been reported.…”
mentioning
confidence: 99%
“…An attractive hypothesis is that the multiple phosphorylation sites in the amino region may govern pp60 C-N activity as part of an interrelated phosphorylation-dephosphorylation network that regulates cellular growth, differentiation, or both. For example, novel mitosis-specific phosphorylations at amino-region threonine and serine residues (4) and at an amino-region tyrosine after treatment with platelet-derived growth factor (11,30) are separately correlated with increased pp60c-'' specific kinase activity. pp60c%I( is also phosphorylated in the amino region by cyclic AMP-dependent protein kinase A (PKA) (6,26) and by the calciumphospholipid-dependent protein kinase, protein kinase C (PKC) (10)(11)(12)39).…”
mentioning
confidence: 99%
See 2 more Smart Citations